The Portfolio Assessment to Teach Writing of Opinion Essay - Setiawan, Anjar; Mulyadi, Dodi (Language Circle: Journal of Language and Literature, 2021)
An opinion essay is a written text to deliver arguments and present supporting evidence to readers. Therefore, this writing activity applies portfolio assessment since it is a cumulative collection of students’ work from beginning to the end. This study aims at describing the implementation of the portfolio to teach the writing of opinion essays at the non-English department in Universitas Muhammadiyah Semarang. The data were collected through observation, tests, and questionnaires. The results showed that the implementation of portfolio assessment could help students write opinion essays by considering its structure and writing components. They were able to state their viewpoint and give supporting data to back up the arguments clearly.